COVID-19 and instability of stock market performance: Evidence from the U.S. - Hui Hong; Zhicun Bian; Chien-Chiang Lee (Financial Innovation, 2021)
The effect of COVID-19 on stock market performance has important implications for both financial theory and practice. This paper examines the relationship between COVID-19 and the instability of both stock return predictability and price volatility in the U.S over the period January 1st, 2019 to June 30th, 2020 by using the methodologies of Bai and Perron (Econometrica 66:47-78, 1998. https ://doi.org/10.2307/29985 40; J Appl Econo 18:1-22, 2003. https ://doi.org/10.1002/jae.659), Elliot and Muller (Optimal testing general breaking processes in linear time series models. University of California at San Diego Economic Working Paper, 2004), and Xu (J Econ 173:126-142, 2013. https ://doi.org/10.1016/j.jecon om.2012.11.001). The results highlight a single break in return predictability and price volatility of both S&P 500 and DJIA. The timing of the break is consistent with the COVID-19 outbreak, or more specifically the stock selling-offs by the U.S. senate committee members before COVID-19 crashed the market. Furthermore, return predictability and price volatility significantly increased following the derived break. The findings suggest that the pandemic crisis was associated with market inefficiency, creating profitable opportunities for traders and speculators. Furthermore, it also induced income and wealth inequality between market participants with plenty of liquidity at hand and those short of funds.
Keywords: C22; G15; G18; 650; COVID-19; Stock returns; Structural breaks; U.S.